Analysis of wind speed data and wind energy potential using Weibull distribution in Zagora, Morocco - Mohammed, Daoudi; Abdelaziz, Ait Sidi Mou; Mohammed, Elkhomri; Elmostapha, Elkhouzai (Center of Biomass & Renewable Energy, Diponegoro University, 2019)
This paper presents the wind energy potential at 10 m during a period of 09 years (2009-2017) in the province of Zagora using the Weibull distribution method. Extrapolation of the 10 m data, using the power Law, has been used to determine the wind data at heights of 30 m; 50 m and 70 m. The objective is to evaluate the most important characteristics of wind energy in the studied site . The statistical attitudes permit us to estimate the mean wind speed, the wind speed distribution function and the mean wind power density in the site at the height of 30 m; 50 m and 70 m. From the primary evaluation indicate that the annual energy output and capacity factor increases with increasing the wind speed, it can obtain about 2.62 GWh/year, that is acceptable quantity for the wind energy. Â©2019. CBIORE-IJRED. All rights reserved